PENGARUH LEVERAGE, UKURAN PERUSAHAAN DAN PERTUMBUHAN ASET TERHADAP NILAI PERUSAHAAN - Nicholas; Susanto, Liana (Jurnal Paradigma Akuntansi, 2025)
The objective of this research is to gather empirical data on how leverage, firm size, and asset growth impact firm value.Property and real estate firms listed on the Indonesia Stock Exchange for the research period 2019–2021 make up the study's population. This study uses purposive sampling method. The sample are 39 firms. The research data are analyzed using multiple linear regression technique which were processed by IBM SPSS 23. The results of this study show that leverage, firm size and asset growth affect firm value simultaneously. Leverage has no clear impact on firm value, however firm size and asset growth have a positive and significant impact. The study's implication is that in order to boost the firm's value and investors' interest, total assets must be increased.